Strategi Mempertahankan Keunggulan Kompetitif pada Produk Perangkat Keras Komputer : Sebuah Studi pada PT. Metrodata e-Business. - , Surya Mukti Suminar, Wakhid Slamet Ciptono, MBA, MPM, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The main purpose of the establishment of a firm is to maximize profits for the welfare of its shareholders and to make any kind of necessary efforts to survive in competition with similar companies. These objectives can be achieved with optimal performance and the company's ability to maintain their competitive advantages, which are advantages that become a differentiating factor for the company from its competitors. The field of strategic management dealing with issues that surrounding on how a company achieve and maintain their competitive advantage. This is because maintaining a competitive advantage is one form of design and implementation of strategies for the company. There are several points of view in identifying the competitive advantage held by the company, but the most popular point of view is the resource-based view or often known as the Resource Based View of The Firm. This point of view is based on the assumption that a company can achieve and maintain a competitive advantage if the company owns and could use resources and capabilities that are spesific or rare as well as canât be imitated or replaced. PT. Metrodata e-Business is a national company that move in the IT field. The company has its own PC brand which is named ION, where itâs intended as a business development, as well as to strengthen local PC brands. This study aims to determine what competitive advantages are owned by PT.Metrodata e-Business and the strategies implemented to maintain it, so the company decided to produce its own brand. The analytical tool used in this study is the Constellation of Competitive Advantage, where competitive advantage is divided into six parts, so it can help to identify the types of competitive advantage held by the company and executable strategies with more clearly.